Julien Green a critical study - O'Dwyer, Michael O. (Four Courts Press, 1997)
Novelist, playwright, author of the longest journals in the history of French literature and member of the Academie Francaise, Julien Green is one of the central figures of twentieth-century French literature. A prolific writer, Green uses classical realism and a visionary perspective to probe the dimensions of despair, anguish, ennui, sin and grace which he sees as being an inherent part of the human condition and to explore what he has called in his journal 'the mystery of the individual'. While Green has written poetically about his love for Paris he remains very much attached to his American origins. In this book Dr Michael O'Dwyer highlights the importance of Green's American background for a full appreciation of his work. Dr O'Dwyer provides a biographical introduction and a critical assessment of the short stories, novels, plays, autobiography, journals and other miscellaneous writings of an author who is among the first rank of modern French writers.
Keywords: Green, Julien <1900-> - Critique et interprétation; Green, Julien <1900-1998> -- Criticism and interpretation; Green, Julien -- 1900-1998